Oliver Bennett, Cultures of Optimism: The Institutional Promotion of Hope. Basingstoke: Palgrave Macmillan, 2015. 248 pp. ISBN: 9781137484802, £60.00. Issue 20 (2015) - Bernstein, Sarah
No abstract available